Four-dimensional flow provides incremental diagnostic value over echocardiography in aortic stenosis - Samer Alabed; Pankaj Garg; Rui Li; Julia Sun; John Curtin; Fabrizio Ricci; Andrew J Swift; Ciaran Grafton-Clarke; Peter Swoboda; David Hewson; Hosamadin Assadi; Rimma Hall; et al. (Open Heart)
Aims Four-dimensional flow cardiovascular MRI (4D flow CMR) has emerged as a promising technique for assessing aortic stenosis (AS). This study aimed to evaluate the agreement between 4D flow CMR and transthoracic echocardiography (TTE) in estimating peak aortic valve (AV) velocities (VPeak), grading AS severity and predicting AV intervention in a real-world setting.Methods Participants from the PREFER-CMR registry who had consecutive TTE and 4D flow CMR were included. AS severity was graded using established protocols using three echocardiographic parameters (VPeak, AV area and mean pressure gradient) and CMR-derived VPeak.Results The study recruited 30 patients (mean age 75.4 years, 67% male), with 17 undergoing AV intervention. Continuous wave Doppler (CWD) VPeak (3.4 vs 2.6 m/s, p=0.0025) and 4D flow VPeak (4.2 vs 2.7 m/s, p<0.0001) were significantly higher in patients going for AV intervention. VPeak by CWD was significantly lower to 4D flow with a bias of −0.5 (p=0.01) and a correlation of (R=0.55, p=0.002). The Cox-regression analysis reveals that 4D flow VPeak significantly predicts AV intervention (HR=2.51, p<0.01), while CWD VPeak (HR=0.54, p=0.76) shows no significant association; overall model fit is significant (χ²=9.5, p=0.02).Conclusion 4D flow CMR-derived VPeak assessment is superior to echocardiographic CWD assessment for predicting timing of AV intervention.Trial registration number NCT05114785.